ANTIMICROBIAL ACTIVITY OF EXTRACTS FROM IN VIVO AND IN VITRO PROPAGATED LAMIUM ALBUM L. PLANTS - Chipeva, Valentina Aleksandrova; Petrova, Detelina Christova; Geneva, Milena Evgenieva; Dimitrova, Milena Angelova; Moncheva, Penka Angelova; Kapchina-Toteva, Veneta Michova (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The antimicrobial activity of 18 different extracts from in vivo and in vitro grown L. album L. plants was evaluated against clinical bacteria and yeasts using the well diffusion method. All the used extracts demonstrated antibacterial activity, whereas only the water extracts from leaves (in vivo) possessed antifungal activity against Candida albicans NBIMCC 72 and Candida glabrata NBIMCC 8673 (14 and 20 mm diameter of inhibition zones and MIC 10 mg/ml, respectively). The methanol and ethanol extracts obtained from the in vitro propagated plants had a broader spectrum of antibacterial activity than those from in vivo plants, while the opposite tendency was observed for the chloroform extracts. All tested flower extracts possessed antimicrobial activity. The chloroform extract from in vivo flowers demonstrated the highest activity against E. faecalis NBIMCC 3915, S. aureus NBIMCC 3703, P. hauseri NBIMCC 1339 and P. aeruginosa NBIMCC 3700 (22 mm, 13 mm, 11 mm, 23 mm zone diameter of inhibition and MIC 0.313 mg/ml, respectively). The water extracts from leaves (both in vivo and in vitro) possessed higher antibacterial activity than extract from flowers. The obtained results showed that both in vivo and in vitro propagated L. album L. could be used as a source of antibacterial substances.